A fast and tuneable auxin‐inducible degron for depletion of target proteins in budding yeast - Mendoza‐Ochoa, Gonzalo I. (Yeast, 2018)
The auxin‐inducible degron (AID) is a useful technique to rapidly deplete proteins of interest in nonplant eukaryotes. Depletion is achieved by addition of the plant hormone auxin to the cell culture, which allows the auxin‐binding receptor, TIR1, to target the AID‐tagged protein for degradation by the proteasome. Fast depletion of the target protein requires good expression of TIR1 protein, but as we show here, high levels of TIR1 may cause uncontrolled depletion of the target protein in the absence of auxin. To enable conditional expression of TIR1 to a high level when required, we regulated the expression of TIR1 using the β‐estradiol expression system. This is a fast‐acting gene induction system that does not cause secondary effects on yeast cell metabolism. We demonstrate that combining the AID and β‐estradiol systems results in a tightly controlled and fast auxin‐induced depletion of nuclear target proteins. Moreover, we show that depletion rate can be tuned by modulating the duration of β‐estradiol preincubation. We conclude that TIR1 protein is a rate‐limiting factor for target protein depletion in yeast, and we provide new tools that allow tightly controlled, tuneable, and efficient depletion of essential proteins whereas minimising secondary effects.